Mitochondrial damage in muscle occurs after marked depletion of glutathione and is prevented by giving glutathione monoester. - Mårtensson, J (1989)
Skeletal muscle degeneration associated with mitochondrial damage was found after marked depletion of glutathione produced by administration to mice of buthionine sulfoximine, an irreversible inhibitor of gamma-glutamylcysteine synthetase. No mitochondrial damage was found in heart. These studies show that in the absence of applied stress (such as ischemia, drug toxicity), very marked depletion (to approximately 3% of the controls) of glutathione must occur before skeletal muscle mitochondria are affected and thus suggest that muscle has a large excess of glutathione. Depletion of glutathione followed a biphasic pattern in skeletal muscle and heart, probably reflecting, in the slow phase, loss of glutathione from mitochondria. Skeletal muscle degeneration did not occur when glutathione monoisopropyl ester was given together with buthionine sulfoximine; it did occur, however, when glutathione was given together with buthionine sulfoximine. Administration of the glutathione monoester (but not of glutathione) prevented the marked decline of mitochondrial glutathione produced by buthionine sulfoximine in skeletal muscle and increased the level of glutathione in heart mitochondria to values higher than the controls. The findings suggest that glutathione monoesters may be useful agents for protection of heart and skeletal muscle against toxicity.